Resisting Violence Emotional Communities in Latin America (Springer International Publishing, 2018)
This book focuses on emotional engagement in academic research with victims of violence and testimonial documentation in Latin America. It examines the recent history of resistance to violence and political repression in Latin America, highlighting the role of emotions in the political sphere. The authors analyse the role of researchers committed to social change and question the mandate of distance and neutrality in academic research in contexts of extreme violence. They use case studies of social resistance to political violence in Mexico, Guatemala, El Salvador, Nicaragua, Colombia and Chile.